Students’ Awareness of Metacognitive Reading Strategies - Rustianingsih*, Noviana; Dangin, Dangin (Universitas Syiah Kuala, 2023)
Since being aware of reading strategies is crucial for readers' success in the process of reading, this study began with the aim of investigating the level of students' awareness of metacognitive reading strategies while dealing with academic reading texts in critical reading and writing class. Through the survey research design, the quantitative research approach is applied. The study includes 40 English department students as the participants. The data were gathered using a Metacognitive Awareness of Reading Strategy Inventory (MARSI-R inventory) questionnaire developed by Mokhtari et al. (2018). The results were interpreted into standard usage levels after each item's score was analysed. The results reveal that of the students are mostly aware of metacognitive reading methods and employ them. In particular, the findings revealed that respondents mostly used Problem Solving Strategies (PROB) to overcome reading obstacles. Support Strategies (SUP) came in second, with the majority of respondents using it. Global Reading Strategies (GLOB) are the final or lowest-level strategies in use.